Studies on German-language islands - Putnam, Michael T. (Studies in language companion series ;, 2011)
The contributions in this volume present cutting-edge theoretical and structural analyses of issues surrounding German-language islands, or Sprachinseln, throughout the world. The individual topics of study in this volume focus on various aspects of these German-language islands such as (but not limited to) phonological, morphological, syntactic, semantic, and pragmatic aspects of these languages under investigation. Collectively, the body of research contained in this volume explores significantly under-researched topics in the fields of language contact and language attrition and illustrates.